Pengembangan Media Pembelajaran Interaktif Menggunakan Articulate Storyline - Romadlon , Dzulfikar Akbar; Farisi, Muhammad Salman Al (Indonesian Journal of Islamic Studies, 2024)
The general background advancement of technology has transformed educational practices, necessitating innovative learning media to engage students effectively. Specific background In the context of Islamic education, particularly in the study of fiqh, there is a growing need for interactive learning tools that can facilitate student understanding and engagement. Knowledge gap However, there is limited research on the application of interactive learning media, such as Articulate Storyline, within pesantren settings to support fiqh education. Aims This study aims to develop and evaluate the use of Articulate Storyline as an interactive learning medium for teaching fiqh in An-Nur Islamic Boarding School. Results The findings demonstrate that Articulate Storyline enhances student engagement and understanding of fiqh concepts by integrating various multimedia elements, such as text, graphics, audio, and video, into the learning experience. Novelty this research highlights the innovative use of Articulate Storyline in Islamic education, providing a structured approach to developing engaging learning media that is responsive to students’ interests and experiences. Implications The study's implications suggest that incorporating interactive learning media can significantly enrich the educational experience in pesantren, encouraging active participation and improving overall learning outcomes. Additionally, it emphasizes the role of educators in utilizing technology effectively to foster critical thinking and analytical skills among students in the learning process. Highlights: Articulate Storyline enhances student engagement through multimedia integration. Interactive learning tools facilitate understanding of fiqh concepts in pesantren settings. Educators play a crucial role in effectively utilizing technology to promote critical thinking. Keywords: Articulate Storyline, Islamic Education, Interactive Learning, Fiqh, Pesantren